Systematic review of contaminants of emerging concern (CECs): Distribution, risks, and implications for water quality and health - Feng, Weiying; Deng, Yuxin; Yang, Fang; Miao, Qing Feng; Ngien, S. K. (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The introduction of contaminants of emerging concern (CECs) into the environment has raised concerns due to the significant risks they pose to both ecosystems and human health. In this sys-tematic review, we investigate research trends on CECs worldwide over the past 10 years, focus-ing on four critical aspects: (i) the identification and distribution of typical CECs across various media, (ii) the sources and environmental behavior of CECs, (iii) the implications of CECs expo-sure on human health, and (iv) risk assessment and control measures for CECs. The review re-veals a comprehensive understanding of the typical types and distribution of CECs in different environmental media, shedding light on their prevalence and potential impact on ecosystems. Furthermore, insights into the sources and behavior of CECs provide crucial information for de-vising effective strategies to mitigate their release into the environment. By examining the health effects of EC exposure, we highlight the importance of considering potential risks to human well-being. This aspect of the review emphasizes the significance of monitoring and managing CECs to safeguard public health. The review also synthesizes the advancements in risk assessment methodologies and control measures for CECs, which are essential for developing comprehensive regulations and guidelines to manage these contaminants effectively. Drawing from the findings, we identify future research directions for CECs in aquatic environments.